Successful treatment of central retinal artery occlusion using hyperbaric oxygen therapy - Kim, Soo Han (Clin Exp Emerg Med, 2018)
Central retinal artery occlusion (CRAO) is considered an ophthalmologic emergency. The prognosis of this disease is very poor. Currently, there is no generally effective therapy available to treat CRAO. Hyperbaric oxygen therapy (HBOT) can increase the volume of oxygen delivered to the ischemic retinal tissue until spontaneous or assisted reperfusion occurs. We report the case of a patient who experienced sudden visual loss due to CRAO that was treated with HBOT. The patient was an 81-year-old woman who presented with CRAO in her right eye (OD). She exhibited “hand motion” visual acuity before treatment. She underwent three sessions of HBOT at a pressure of 2.8 atmospheres absolute, performed over 3 days. After 4 days in hospital, her visual acuity improved to 0.4 (OD) for far vision and 0.5 (OD) for near vision. Her vision was stable without the supply of oxygen; therefore, she was discharged.